2017
DOI: 10.1097/j.pain.0000000000000832
|View full text |Cite
|
Sign up to set email alerts
|

A novel inhibitor of active protein kinase G attenuates chronic inflammatory and osteoarthritic pain

Abstract: Supplemental Digital Content is Available in the Text.A novel and potent protein kinase G-1α (PKG-1α) inhibitor is used to demonstrate the important roles of PKG in capsaicin-induced acute pain and in persistent inflammatory pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…In particular, Phe-350 at the glycine-rich loop occupies the part of the pocket the C-ring binds, suggesting that N46 would interact poorly with PKC␣. Consistent with the model, Sung et al (18) reported that, at 0.75 M of N46, PKC␦ had 68% residual activity, whereas PKG I␣ was completely inhibited with 0% residual activity .…”
Section: N46 Specificity For Pkg I␣mentioning
confidence: 57%
See 4 more Smart Citations
“…In particular, Phe-350 at the glycine-rich loop occupies the part of the pocket the C-ring binds, suggesting that N46 would interact poorly with PKC␣. Consistent with the model, Sung et al (18) reported that, at 0.75 M of N46, PKC␦ had 68% residual activity, whereas PKG I␣ was completely inhibited with 0% residual activity .…”
Section: N46 Specificity For Pkg I␣mentioning
confidence: 57%
“…The reported inhibition constant of balanol for PKA C␣ is 1.6 nM, whereas N46 inhibits PKA with an IC 50 of 1.0 M, showing an over 600-fold increase (18). Comparing the PKA C␣-N46 complex with the PKA C␣-balanol complex reveals that this reduction is mostly due to loss of hydrogen bonds (Fig.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations